• Предмет: Математика
  • Автор: kololot170
  • Вопрос задан 7 лет назад

Помогите решить пожалуйста.

frac{x}{y} (frac{y}{x} - frac{x}{y} (frac{y^2}{x^2} - frac{x}{y} ( frac{y^3}{x^3} - frac{y^4}{x^4} )))

Ответ должен выйти: frac{x-y}{x} 

Ответы

Ответ дал: julyap
0
 frac{x}{y} *( frac{y}{x} - frac{x}{y} ( frac{y ^{2} }{ x^{2} } - frac{x}{y} ( frac{ y^{3} }{ x^{3} } - frac{y ^{4} }{ x^{4} } )))= frac{x-y}{y}

1)  frac{y ^{3} }{ x^{3} } - frac{y ^{4} }{ x^{4} } = frac{xy ^{3}-y ^{4}  }{ x^{4} } = frac{y ^{3} (x-y)}{ x^{4} } \  \ 2)  frac{x}{y} * frac{y ^{3}(x-y) }{ x^{4} }  = frac{y ^{2}(x-y) }{ x^{3} } = frac{xy ^{2} -y ^{3} }{ x^{3} }  \  \ 3)  frac{y ^{2} }{ x^{2} } - frac{xy ^{2}-y ^{3}  }{ x^{3} } = frac{xy ^{2}-xy ^{2}+y ^{3}}{ x^{3} }= frac{y ^{3} }{ x^{2} } \  \ 4)  frac{x}{y} * frac{y ^{3} }{ x^{3} } = frac{y ^{2} }{ x^{2} }  \  \

5)  frac{y}{x} - frac{y ^{2} }{ x^{2} } =  frac{xy-y ^{2} }{ x^{2} } = frac{y(x-y)}{ x^{2} }  \  \ 6)  frac{x}{y} * frac{y(x-y)}{ x^{2} } = frac{x-y}{x}

Похожие вопросы